ESTABLISHING THE ENERGY BALANCE FOR THE STEAM GENERATOR - Dan Codrut PETRILEAN; Andreea TATARU (Fiabilitate şi Durabilitate)
In the paper, the real hourly thermal energy balance of a steam generator was designed to establish energy performance indicators. They have been compared with the prospectus data. Following the observed differences, technical and organizational measures have been proposed to improve the energy efficiency of the steam generator. Diagrams showing the variation of efficiency and specific heat consumption depending on the thermal load, as well as the dependence of the heat consumption on the fuel depending on the steam flow rate, were also conceived